FITNESS TECHNOLOGIES IN THE DEVELOPMENT OF PHYSICAL QUALITIES OF WOMEN AGED 40–55: A COMPREHENSIVE APPROACH - BURNES Lyubov Anatolyevna («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article presents the results of an experiment conducted at the National University of Uzbekistan over one academic year to test the eﬀectiveness of various "ftness training" programs for women aged 40–55. The data obtained allowed us to evaluate the impact of various training regimens on the physical development and general health of mature women.